An introduction to model-based survey sampling with applications - Chambers, R. L. (Ray L.); Clark, Robert G. (Oxford : Oxford University Press, 2012)
This text brings together important ideas on the model-based approach to sample survey, which has been developed over the last 20 years.
Description based on print version record.
Keywords: Sampling (Statistics); Sampling (Statistics) -- Mathematical models; Mathematical statistics